(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
We now have a plethora of programming languages to meet our requirements, but the most pressing issue is how to teach programming to beginners. We recommend Python for this job in this article since it is a programming language with a well-organized syntax and strong capabilities for solving any problem. Furthermore, it is extremely similar to basic math reasoning. In most top institutions, Python is selected as the main programming language for freshmen. Python makes it simple to write code. In this article, we provide several computer code samples developed in Java, C++, and Python, as well as a comparison of the three languages.To begin, this article discusses the benefits of Python over C++ and Java. The results of a comparison of brief program codes written in three distinct languages are then shown, followed by a discussion of how pupils comprehend programming. Finally, the experimental findings of students’ programming course success are shown.